2014
DOI: 10.1007/s00365-014-9238-2
|View full text |Cite
|
Sign up to set email alerts
|

Well-Separated Spherical Designs

Abstract: For each N ≥ C d t d we prove the existence of a well-separated spherical t-design in the sphere S d consisting of N points, where C d is a constant depending only on d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 20 publications
0
60
0
Order By: Relevance
“…Bondarenko, Radchenko and Viazovska [9] have shown that on S d well-separated spherical t-designs exist for N ≥ c d t d . This combined with Yudin's result on the covering radius of spherical designs mean that there exist spherical t-designs with N = O(t d ) points and uniformly bounded mesh ratio.…”
Section: Geometric Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Bondarenko, Radchenko and Viazovska [9] have shown that on S d well-separated spherical t-designs exist for N ≥ c d t d . This combined with Yudin's result on the covering radius of spherical designs mean that there exist spherical t-designs with N = O(t d ) points and uniformly bounded mesh ratio.…”
Section: Geometric Qualitymentioning
confidence: 99%
“…2. These tables also list both the Delsarte, Goethals and Seidel lower bounds N * (2,t) and the Yudin lower bound N + (2,t), plus the actual number of points N. The number of points N = N(2,t), apart from t = 3, 5, 7,9,11,13,15 when N = N(2,t) − 1. There may well be spherical t-designs with smaller values of N and special symmetries, see [35] for example.…”
Section: Structure Of Point Setsmentioning
confidence: 99%
“…The construction is not limited to S 2 (because [11] is done in full generality on S d ). The same argument yields, for all d ≥ 2, all n ≥ 2 and for all 0 < t ≤ c d n −2/d a function f t ∈ C ∞ (S d ) such that f is orthogonal to the first n eigenfunctions of −∆ S d−1 and…”
Section: Proof Of the Propositionmentioning
confidence: 99%
“…For many cardinalities close (but not equal) to D(n, τ ) existence of spherical τ -designs is still an open problem. On the other hand, existence of designs with asymptotically optimal cardinalities was proved by Bondarenko, Radchenko, and Viazovska [6,7].…”
Section: Delsarte-goethals-seidel Bound and Polynomialsmentioning
confidence: 99%